Pengaruh Pembiayaan Mikro Terhadap Perkembangan Usaha Mikro Kecil Menengah (UMKM) - Muhammad Arif; H Hardiyanti (TANSIQ: Jurnal Manajemen Dan Bisnis Islam, 2020)
This study aims to determine the effect of micro-financing on the development of UMKM in Lawe Alas District. This research is measured by several indicators such as the amount of business capital received, an increase in sales turnover, an increase in the number of workers, an increase in profits, an increase in the workforce and the ability to open business branches. The method of data analysis was carried out using a simple linear regression analysis method, namely to determine the effect of the independent variable Micro financing on the dependent variable of UMKM development which was tested separately. And based on the results of data processing shows that analyzing the influence of micro financing on the development of UMKM in Lawe Alas District has a positive influence of 53%.